ChemInform Abstract: Acetanilide Palladacycle: An Efficient Catalyst for Room‐Temperature Suzuki—Miyaura Cross‐Coupling Reaction. Issue 35 (2nd September 2014) - Dewan, Anindita; Buragohain, Zenith; Mondal, Manoj; Sarmah, Gayatri; Borah, Geetika; Bora, Utpal
Abstract 4‐Tolyl and 4‐chlorophenyl acetamide derivatives of the phenyl acetamide palladacycle PAP show lower catalytic activities.